Penguatan Kapasitas Masyarakat untuk Pengelolaan Desa Wisata Mandiri Berkelanjutan - Hary Firmansyah; Aditya Tri Maulana; Rizki Nur Iman; Dacep Perdiansyah; Ardian Fathan Arrahman; Jaohara Wianda (Journal of Empowerment Community, 2026)
The purpose of this activity was to increase the capacity of natural resource management in Tanjungsari Village by introducing the location of tourist attractions through sitemaps created on the Google Maps feature, as an effort to promote regional tourism that will become the flagship of Tanjungsari Village in an effort to increase the attraction and economic resources that could be felt by residents in the local area through the optimization of natural resources managed by the tourism awareness group from the local youth organization. The method used in this activity was a participatory method that involves the participation of the local community to play an active role in the succession of activities carried out. From the implementation of this activity, it could be concluded that the program implemented has succeeded in increasing awareness and active participation of the community in optimizing natural resources as a basis for improving the community's economy through the natural tourism sector which is still in the stage of further development by the local government. Therefore, this activity requires further development carried out periodically by various parties.